Perceptions of aspiring Malaysian principals on transactional, transformational and instructional leadership behaviours - Lope Pihie, Zaidatol Akmaliah; Elias, Habibah (Universiti Putra Malaysia Press, 2002)
The purpose of this study was to determine the degree to which aspiring school principals will practise transactional, transformational and instructional leadership behaviour in managing secondary schools. Data were collected from 89 graduate students enrolled in the leadership course for the masters programme in Educational Administration conducted at UPM Serdang. They came from different parts of Malaysia and had teaching experience in 89 different schools. Findings indicated that aspiring secondary school principals perceived themselves as capable of adopting transformational leadership style. Results indicate that these participants scored high on all aspects of transformational leadership behaviour such as inspirational motivation, charisma, intellectual stimulation, and individual consideration. With regard to instructional leadership responsibilities, findings indicated that the aspiring principals scored high on providing an orderly atmosphere for learning and emphasizing student achievement. However, their inclination towards improving and evaluating teachers' performance was low. This study suggests certain measures to improve the Malaysian school leaders practice for school effectiveness.